Exploring the multifaceted roles of GLP-1 receptor agonists; a comprehensive review - Bisma Fatima Hammad; Nimrah Zafar; Muneeb Ullah; Syeda Jazilah Faisal; Fizzah Iftikhar; Haadia Waheed; Muhammad Waleed Muzaffar; Khadija Ahmed; Faz Ashraf; Komal Zahid; Maimoona Akhtar; Mohammed Mahmmoud Fadelallah Eljack (Frontiers in Clinical Diabetes and Healthcare)
Traditionally, Glucagon-like peptide-1 (GLP-1) receptor agonists (GLP-1RAs), a pivotal class of drug, mimics the actions of endogenous Glucagon-like peptide-1, which have been found to be remarkable in the treatment of type 2 diabetes alongside other comorbidities. GLP-1 receptors being widely available in the different organs and tissues such as the brain, lung, pancreas, stomach, heart, and endometrium has explained the broader therapeutic application of GLP-1RA. The recent studies have explored the physiological effects of GLP-1RA on body organs, establishing them as a potential therapeutic option for a wide range of diseases. Activation of GLP-1 receptors contribute to regulation of blood glucose levels, weight management, cardiovascular health, and potential neuroprotection, while also having a positive influence on musculoskeletal health. This review has emphasized the expanded role of GLP-1RA by highlighting the most significant and notable studies. While GLP-1RA has proven clinical efficacy, the need for more comprehensive studies, to ensure their long-term safety, is essential to optimize their therapeutic role and improve patient outcomes on a global scale. Addressing the significant gap for research on cost effectiveness of these drugs is also crucial for their accessibility in comparison to other drugs. Nevertheless, the limited data available calls for a platform for future research to carry out the expanded therapeutic effects of GLP-1RA.